Dendritic cells infected by recombinant modified vaccinia virus Ankara retain immunogenicity in vivo despite in vitro dysfunction. - Behboudi, S; Moore, A; Gilbert, S; Nicoll, C; Hill, A (2004)
The administration of recombinant vaccinia virus Ankara (MVA) encoding a CTL epitope (pb9) from a malaria antigen induced activation and maturation of splenic dendritic cells (DCs) in vivo. In contrast, incubation of immature dendritic cells (iDCs) with the MVA, in vitro, resulted in down-regulation of MHC class I molecules and reduced their T-cell stimulatory ability. However, the ability of the infected DC to induce an antigen-specific CTL response, in vivo, remained intact. Furthermore, the administration of recombinant MVA-infected DC, but not pb9 peptide-pulsed DC, boosted and expanded the anti-pb9 CTL response that was primed by pb9 peptide-pulsed DC. These data indicate that despite the ability of poxviruses to impair DC maturation in vivo, the important ability of MVA to boost CD8 T-cell response in vivo is mediated at the level of the infected dendritic cells.